Statistical approach of Ca2+ effect on the amylases production by Saccharomyces diastaticus ATCC 13007 using corn and cassava starch as inducers - Solange Cristina Carreiro; Ana Letícia Silva Coelho; Agelles Alves Arraes; Thiago Lucas de Abreu-Lima (Acta Biológica Catarinense, 2021)
Amylase production from starch sources is associated with the nature of this carbon source, particle size and crystalline architecture of natural starch granules. The aim of this work was to evaluated the amylase production by Saccharomyces diastaticus ATCC 13007, using different CaCO3 concentration and corn starch (Zea mays) and cassava starch (Manihot esculenta) as inducers. A 22 Central Composite Rotatable Design with three replications at the center point was used to determine the influence of calcium and starch concentrations on the production process. Besides, the partial characterization of the crude enzymatic extracts obtained was investigated. Ca2+ influenced the α-amylase production by both evaluated carbon sources. The production of glucoamylase was not influenced by the variables under study. Partial characterization of crude extracts indicated that, for corn substrate, the enzyme showed maximum activity at pH 5.0, and no influence of temperature was observed. Regarding cassava starch, the results showed that conditions at central point (pH 6.5 and 50ºC) should be avoided in order to maximize enzyme activity.